Objectives, structure and subject of a methodological planning - Belyaev, Anton Alekseevich (Tambov University Review. Series: Humanities, 2018)
The research is devoted to the full review of the notion of a methodological planning. This research is very actually now because despite a big using of the methodological planning in modern educational institutions, this notion stays insufficiently explored from theoretical point of view. The theoretical basis of this notion allows to use it completely and correctly in practice. This research is based on the methods of the theoretical and comparative analyses. Different opinions and comments of Russian and foreign scientists, who examine the general fact of the planning and the methodological and pedagogical planning, are studied. It was found that the methodological planning is a part of the larger notion - the pedagogical planning. At plus the methodological planning is one of the stages of the pedagogical process which is a part of the pedagogical system. As illustrations some examples of the methodological planning’s using in schools and in universities of the Russian Federation were used. It was proved that the methodological planning is one of the most important stages of the pedagogical process. In virtue of the comparative analysis of the definitions of others authors, our own definition of the methodological planning is offered. As example of the sequential algorithm stages of the methodological planning and possible ways of its realization were studied. It is necessary to use the methodological planning in the pedagogy for the realization of the most important purpose of a pedagogical process - it is the good knowledge assimilation by pupils and students.